2020
DOI: 10.1080/10408347.2020.1781592
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Methods on Determination in Pharmaceuticals and Biological Materials of Chloroquine as Available for the Treatment of COVID-19

Abstract: With the outbreak caused by the severe acute respiratory syndrome coronavirus (COVID-19), people's health and existing economies on a global scale are seriously threatened. Currently, most of the countries all over the world are studying extensively to better understand the antimalarial chloroquine (CQ) and hydroxychloroquine (HCQ) for therapeutic purposes due to the COVID-19 outbreak. However, CQ and HCQ can have serious side effects, from psychiatric effects to sudden death. Therefore, a faster and more effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 102 publications
0
7
0
Order By: Relevance
“…The use of analytical technology tools like mass spectrometers including orbitrap, quadruple with linear ion-trap, and quadruple with time-of-flight could detect some low concentrations of the pollutants in the environmental samples (Reyes et al 2021 ; Rosal et al 2010 ). Recently, Saka ( 2020 ) reviewed different chloroquine quantitative determination and detecting techniques including chromatography, electroanalytical, electrophoresis, ELISA (Saka 2020 ). High-performance liquid chromatography is one of the most frequently used detection techniques (Saka 2020 ) and electroanalytical methods are highly significant mainly in situ analysis of chloroquine and other PPCPs in effluent and surface water.…”
Section: Detection Determination and Extraction Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of analytical technology tools like mass spectrometers including orbitrap, quadruple with linear ion-trap, and quadruple with time-of-flight could detect some low concentrations of the pollutants in the environmental samples (Reyes et al 2021 ; Rosal et al 2010 ). Recently, Saka ( 2020 ) reviewed different chloroquine quantitative determination and detecting techniques including chromatography, electroanalytical, electrophoresis, ELISA (Saka 2020 ). High-performance liquid chromatography is one of the most frequently used detection techniques (Saka 2020 ) and electroanalytical methods are highly significant mainly in situ analysis of chloroquine and other PPCPs in effluent and surface water.…”
Section: Detection Determination and Extraction Methodsmentioning
confidence: 99%
“…Recently, Saka ( 2020 ) reviewed different chloroquine quantitative determination and detecting techniques including chromatography, electroanalytical, electrophoresis, ELISA (Saka 2020 ). High-performance liquid chromatography is one of the most frequently used detection techniques (Saka 2020 ) and electroanalytical methods are highly significant mainly in situ analysis of chloroquine and other PPCPs in effluent and surface water. In a recently advanced carbon-graphene-based sensor, Lorenzetti et al detected tetracycline in very concentration using reduced graphene oxide (Lorenzetti et al 2020 ), Setznagl and Cesarino detected low concentrations of estriol hormone and glyphosate in water sample using reduced graphene oxide–metal nanoparticle (Setznagl and Cesarino 2020 ).…”
Section: Detection Determination and Extraction Methodsmentioning
confidence: 99%
“…A recent state-of-the-art review (Saka, 2020) into the detection techniques and quantitative determination methods for CQ and its related metabolites found that the main methods used for CQ analysis are liquid chromatography, capillary electrophoresis, electroanalytical, spectrophotometric, and ELISA-based methods. In most of the studies, detection and quantification of CQ were performed in pharmaceutical dosage formulations and biological matrices and the most frequently used technique is high performance liquid chromatography (HPLC).…”
Section: Detection and Quantification Of Covid-19 Relevant Pharmaceut...mentioning
confidence: 99%
“…These assays would not only be much quicker than the classic setups, but also would be very cost efficient since much smaller amounts of reagents are used on these purposes [171] . As an example, 25,000 or even more gene sequences could now be analyzed simultaneously using just one DNA microarray chip, so more sequence per cost and time could be adequately analyzed [172] . Regarding to this concept, biosensors have been initially defined as a self-contained integrated device that has the ability to produce specific qualitative, quantitative or semi-quantitative analytical information via biological target interaction/reaction directly or indirectly with the transducer [173] .…”
Section: The Level Of Os and Related Compoundsmentioning
confidence: 99%